Updated constraints on sterile neutrino mixing in the OPERA experiment using a new νe identification method. (24th January 2023) - ,; Agafonova, N; Alexandrov, A; Anokhina, A; Aoki, S; Ariga, A; Ariga, T; Bertolin, A; Bozza, C; Brugnera, R; Buontempo, S; Chernyavskiy, M; et al.
Abstract: This paper describes a new ν e identification method specifically designed to improve the low-energy (30 GeV ) ν e identification efficiency attained by enlarging the emulsion film scanning volume with the next-generation emulsion readout system. A relative increase of 25–70% in the ν e low-energy region is expected, leading to improvements in the OPERA sensitivity to neutrino oscillations in the framework of the 3 + 1 model. The method is applied to a subset of data where the detection efficiency increase is expected to be more relevant, and one additional ν e candidate is found. The analysis combined with the ντ appearance results improves the upper limit on sin 2 2θμ e to 0.016 at 90% C.L. in the MiniBooNE allowed region Δ m^2_41 0.3 eV^2 .